Flexural behavior of precast, prestressed, lightweight aggregate concrete-conventional concrete composite beams. (8th March 2021) - Li, Shiping; Chen, Wujun; Zhang, Yibei
Highlights: The bearing capacity of LAC-CC composite beams can be designed according to the plane-section assumption. The cracking moment formula applicable to LAC-CC composite beams was proposed. The applicability of the method for calculating the ultimate bearing capacity of conventional concrete beams in GB50010-2010 was verified. The formulas for average crack spacing and average crack width were derived. Abstract: This study explores the flexural behavior of precast, prestressed, lightweight aggregate concrete-conventional concrete composite beams. Ten specimens were tested with consideration of the height of the combined interface, the reinforcement ratio, and the location of the lightweight-aggregate concrete. Failure modes, bearing capacities, deformation characteristics, and crack widths were observed, and the influences of various parameters on flexural performance are discussed. The results show that the bending process of lightweight aggregate concrete-conventional concrete composite beams is similar to that of conventional concrete beams. There is no slip failure at the combined interface, the flexural capacity of a lightweight aggregate concrete-conventional concrete composite beam can be calculated based on the plane-section assumption. Considering the proportion of lightweight-aggregate concrete in the lightweight aggregate concrete-conventional concrete composite beam and combined with the cracking moment calculation formula in GB50010-2010, a cracking moment formula applicable to lightweight aggregate concrete-conventional concrete composite beams is proposed. The applicability of the method for calculating the ultimate bearing capacity of conventional concrete beams in GB50010-2010 is verified. Based on regression analysis of test data and the introduction of a comprehensive coefficient of influence C m, formulas for average crack spacing and average crack width are derived, which lays a theoretical foundation for further engineering applications.